PEMBELAJARAN MANAJEMEN KELAS HUMANISTIK MELALUI LITERATUR NARATIF: REFLEKSI MAHASISWA CALON GURU TERHADAP BUKU TOTTO-CHAN - Nurhasanah, Nurhasanah; Nurul Atik Hamida; Linda Kusumawati; Elvin Cahyanita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Studies on classroom management in teacher education have predominantly focused on technical strategies and field-based practices, while the potential of narrative literature as a medium for pedagogical reflection remains underexplored. This study aims to explore pre-service teachers’ reflections on humanistic classroom management values derived from reading the novel Totto-chan: The Little Girl at the Window by Tetsuko Kuroyanagi. A qualitative descriptive approach was employed to capture participants’ reflective experiences and interpretations. The participants were pre-service teachers enrolled in a Classroom Management course at a teacher education program in Indonesia, selected through purposive sampling. Data were collected through written reflections and semi-structured interviews, and analyzed using thematic analysis. The findings reveal four main themes: (1) appreciation of students’ individuality and creativity, (2) freedom and flexibility in learning, (3) positive approaches to managing student behavior, and (4) the role of the teacher as a facilitator and learning guide. These findings indicate that narrative literature plays a significant role in shaping pre-service teachers’ reflective and humanistic perspectives on classroom management. Through narrative engagement, students were able to understand classroom management practices in a contextual, empathetic, and meaningful way, leading to a paradigm shift from control-oriented approaches toward student-centered and developmental perspectives. Therefore, narrative literature can be considered an effective alternative pedagogical resource in classroom management learning within teacher education